On pulse solutions of a reaction–diffusion system in population dynamics. (June 2015) - Volpert, V.; Reinberg, N.; Benmir, M.; Boujena, S.
Abstract: A reaction–diffusion system of equations describing the distribution of population density is considered. The existence of pulse solutions is proved by the Leray–Schauder method based on the topological degree for elliptic operators in unbounded domains and on a priori estimates of solutions. Numerical simulations show that such solutions become stable in the case of global consumption of resources while they are unstable without the integral terms. This model is used to describe human height distribution.